Penggambaran Insecurity pada Film Animasi Ralph Breaks The Internet - Raynaldy Fernando; Syaifuddin (UNIVERSITAS KALBIS, 2022)
Insecurity is a problem that is often experienced by humans, this involves feeling afraid and also inferior to their environment which causes interference with a relationship or a person's mood and feelings. In the film Ralph Breaks The Internet also provides an overview of insecurity. Based on these problems, this study aims to determine the insecurity picture that appears in the scenes in the film Ralph Breaks The Internet, by using social reality construction theory and Charles S. Peirce's semiotic analysis method (sign, object, interpretant). The approach used in this research is qualitative with the constructivism paradigm. The results of this study found that insecurity in the film Ralph Breaks The Internet is depicted in several forms starting from a fear, the effect of fear and also as an atmosphere or mood, and then in the form of a rejection as a concrete picture of insecurity.